Identifying the priorities in nursing research on disaster management: A Delphi study and international survey. (May 2022) - Molassiotis, Alex; Guo, Chunlan; West, Caryn; Loke, Alice Yuen
Abstract: The aim in this study was to explore and determine the priorities in nursing research for disaster management. A systematic literature review was conducted to identify and compile a list of statements on research priorities in disaster nursing. Next, a Delphi survey was conducted among experts identified from international disaster nursing professional societies and disaster nursing education programs to obtain their insights on the priorities in nursing research for disaster management. Lastly, an international web-based survey was conducted to collect data from frontline nursing practitioners, researchers, educators, and leaders. Through the systematic literature review, 327 research statements on disaster-related issues were derived from 28 publications. The Delphi survey generated a final list of 90 nursing research statements on disaster management. There were 133 responses to the web-based survey from 26 different countries/areas. The top three research priorities were "education and preparedness in the nursing profession" (mean = 4.45, SD = 0.79), "nurses' competency to respond to disasters" (mean = 4.44, SD = 0.82), and "emergency management planning in healthcare, community and aged care facilities" (mean = 4.40, SD = 0.84). Significant differences were observed among those of different age groups, lengths of experience in disaster management, primary work settings, affiliated nursing society memberships, and WHO regions. The findings of this research provide a general picture of the priorities in nursing research for disaster management, and led to the identification of the overarching research priorities in this area and of areas in need of further research. Furthermore, it provided valuable suggestions for funding organizations and policymakers to decide on those areas of disaster nursing that warrant further research.